Key Indicators Driving Innovative Growth in the Green Economy - Djanzakovich, Mirzayev Kulmamat (Academia Open, 2025)
General Background: Addressing the global imperative of harmonizing economic growth with environmental sustainability, the concept of a green economy has gained international traction. Specific Background: Rooted in ecological economics, the green economy emphasizes resource efficiency, renewable energy, and social equity, offering a strategic framework for sustainable development. Knowledge Gap: Despite the global momentum, emerging economies like Uzbekistan face challenges in implementing green transitions due to limited institutional capacity, financing constraints, and insufficient innovation infrastructure. Aims: This study investigates the indicators, policies, and practices driving innovative green economic development, with a focus on Uzbekistan’s transition strategies and international benchmarks. Results: The findings underscore the positive economic impact of green policies, including potential job creation (up to 270,000 green jobs by 2050), renewable energy investments exceeding $5 billion, and advancements in waste management, transportation, and agriculture. Novelty: The paper presents a comprehensive model integrating global best practices with national-specific strategies, supported by the World Bank-funded iCRAFT project. Implications: The results inform policy on fostering low-carbon growth, enhancing green innovation, and ensuring equitable access to green development benefits. Uzbekistan’s evolving framework positions it to become a regional leader in sustainable economic transformation. Highlight : Policy Integration – Strategic planning and government support are vital to transitioning into a green economy. Innovation Impact – Green technologies like smart grids and fintech drive sustainable growth. Job Creation – Green sectors are projected to generate over 270,000 jobs in Uzbekistan by 2050. Keywords : Green Economy, Sustainability, Innovation, Renewable Energy, Uzbekista